Determination of prevalence and antibiotic susceptibility pattern of bacteria isolated from household and restaurant kitchen utensils of Dhaka, Bangladesh - Anwar, Tashfia (BRAC Univeristy, 2018)
This thesis report is submitted in partial fulfilment of the requirement for the degree of B.Sc in Microbiology, 2018.